Please Sign to Save... : How Online Environmental Petitions Succeed - Proskurnia, Julia; Aberer, Karl; Cudré-Mauroux, Philippe (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
Social media have become one of the key platforms to support the debate on climate change. In particular, Twitter allows easy information dissemination when running environmental campaigns. Yet, the dynamics of these campaigns on social platforms still remain largely unexplored. In this paper, we study the success factors enabling online petitions to attain their required number of signatures. We present an analysis of e-petitions and identify how their number of users, tweets and retweets correlate with their success. In addition, we show that environmental petitions are actively promoted by popular public campaigns on Twitter. Finally, we present an annotated corpus of petitions posted by environmental campaigns together with their corresponding tweets to enable further exploration.